2017
DOI: 10.11609/jott.3091.9.9.10649-10655
|View full text |Cite
|
Sign up to set email alerts
|

<b>Distribution and habitat use of the endangered Dhole <I>Cuon alpinus</I> (Pallas, 1811) (Mammalia: Canidae) in Jigme Dorji National Park, western Bhutan</b>

Abstract: C omm u n fi c a t fi o n D fi s t r fi b u t fi o n a n d h a b fi t a t u s e o f t h e e n d a n g e r e d D h o l e C u o n a l p fi n u s ( P a l l a s , 1 8 1 1 ) (M amm a l fi a : C a n fi d a e ) fi n J fi gm e D o r j fi N a t fi o n a l P a r k , w e s t e r n B h u t a n C h h fim fi N am g y a l & P h u n t s h o T h fi n l e y 2 6 S e p t em b e r 2 0 1 7 | V o l . 9 | N o . 9 | P p . 1 0 6 4 9 -1 0 6 5 5 1 0 . 1 1 6 0 9 / j o t . 3 0 9 1 . 9 . 9 . 1 0 6 4 9 -1 0 6 5 5 T h r e a t e n e d T a x a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…We then used the tiger occurrence points in MaxEnt by correlating them with input variables (Table 2) to produce a probability surface of tiger occurrence (Elith et al, 2010). In line with Namgyal and Thinley (2017), we used the default settings in the MaxEnt model comprising 500 interactions, a 0.00001 convergence threshold, 1 regularization multiplier, and 10,000 background points with 50% random test percentage. This was exported to ArcMap and reclassified into a suitability surface.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We then used the tiger occurrence points in MaxEnt by correlating them with input variables (Table 2) to produce a probability surface of tiger occurrence (Elith et al, 2010). In line with Namgyal and Thinley (2017), we used the default settings in the MaxEnt model comprising 500 interactions, a 0.00001 convergence threshold, 1 regularization multiplier, and 10,000 background points with 50% random test percentage. This was exported to ArcMap and reclassified into a suitability surface.…”
Section: Methodsmentioning
confidence: 99%
“…Because of its status as a national priority species (Wang & Macdonald, 2009), landscape-level tiger studies in Bhutan have mainly focused on population (Tempa, Hebblewhite, Goldberg, et al, 2019;Thinley, Dorji, Tempa, et al, 2015) and movement dynamics (Thinley et al, 2020), as conducted elsewhere in South India (Gubbi et al, 2016), China (Wang et al, 2018), and the Terai Arc Landscape straddling Nepal and India (Thapa, Wikramanayake, Malla, et al, 2017). In an effort to maintain viable tiger populations, some studies have additionally prioritized assessment of landscape connectivity through various approaches such as mapping potential forest loss in Sumatra (Poor, Shao, & Kelly, 2019), investigating metapopulation gene flow in central India (Seidensticker, 2016), and spatially identifying corridors in western India (Mondal, Habib, Talukdar, & Nigam, 2016). More recently, Sanderson, Moy, Rose, et al (2019) even investigated shared socioeconomic pathways to gauge the influence of human population growth on tiger conservation.…”
Section: Introductionmentioning
confidence: 99%
“…Several modeling studies on dhole distribution and occupancy have been carried out at varying scales. At local scales, parkwide potential dhole distribution modeling was carried out by Namgyal and Thinley (2017) in Bhutan's Jigme Dorji National Park and by Rahman et al (2018) in Indonesia's Ujung Kulon National Park, whereas Singh et al (2020) recently reported on dhole occupancy in India's Dampa Tiger Reserve. At the broader landscape scale, Srivathsa et al (2014), Punjabi et al (2017), andSrivathsa et al (2019a) modeled dhole occupancy across the Western Ghats of Karnataka, India.…”
Section: Introductionmentioning
confidence: 99%
“…There is no current population estimate for dholes in Bhutan. They were, however, almost extirpated from the country in the 1970s and 80s by mass poisoning campaigns due to blames over persistent livestock depredation (Wang and Macdonald, 2006;Thinley et al, 2011;Namgyal and Thinley, 2017). Because dholes are known to control populations of wild pig (Sus scrofa), the principal crop-raiding species in Bhutan (Wangchuk, 2004;Thinley et al, 2018), it is believed that wild pig populations in Bhutan substantially increased and intensified crop damage after the mass extermination of dholes (Wangchuk, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation